ISOLASI, IDENTIFIKASI, DAN PENETAPAN KADAR TOTAL FLAVONOID DARI FRAKSI ETIL ASETAT DAUN JINTEN (Coleus amboinicus Lour.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Marinus Kurniawan Adi Widiarto (2023)
Cumin leaves (Coleus amboinicus Lour.) contain various chemical compounds proven to provide many benefits, one of which is as an antioxidant. These properties are known from the presence of flavonoid compounds contained in the leaves. This study aims to isolate, identify, and determine the total levels of flavonoids from the ethyl acetate fraction of cumin leaves. Isolation of flavonoid compounds was started by ultrasonic extraction with variations in temperature (45, 60, and 75oC) and extraction time (10, 15, and 20 minutes), then carried out yield analysis, phytochemical screening tests, and total flavonoid content tests. The extract with the highest total flavonoid content was then separated by fractionation using n-hexane, ethyl acetate, and water as solvents. Flavonoids in the ethyl acetate fraction were then separated by preparative TLC with the eluent n-butanol : acetic acid : water (4 : 1 : 5). Identification of flavonoids using a UV-Vis spectrophotometer with quercetin as a reference standard. The results of the total flavonoid content of the ethyl acetate fraction of cumin leaves were 208.96 mQE/gram, the preparative TLC test showed that there was one spot that was the same as the quercetin standard. The stain is greenish yellow at Rf 0.673, almost the same as the standard quercetin stain at Rf 0.667. The results of the identification of isolates can be suspected that the flavonoid compound is a flavonol group with a wavelength range between 350 - 385 nm (band I) and 250 - 280 nm (band II). Keywords: cumin leaves, flavonoid, ultrasonic extraction, UV-Vis spectrophotometry